The Fatality Rate of COVID-19: How Does Education, Health Infrastructure and Institutional Quality Make a Change?. (May 2022) - Tang, Chor Foon; Fakih, Ali; Abosedra, Salah
This article provides new empirical evidence on the impact of institutional quality in affecting female fatality rates resulting from COVID-19 by grounding our analysis on the marginal effects on other explanatory variables. This strain of research is not well examined in existing literature. We identify the main determinants of these rates and empirically estimate several models using cross-country data for 2020 for 57 countries. Our results show that not allowing for such marginal effects seems to produce imprecise results whereby institutional quality returns to be insignificant in explaining the fatality rates from COVID-19 and thus may have resulted in inappropriate policy recommendations from previous studies. Our results extend recent findings on the role of institutional quality in reducing female fatality rates and imply that benefits expected from improvements in institutional quality are worthy of consideration and implementation. The article offers some recommendations based on the reported results. JEL Codes: C36, I15, I18